Rare ectopic metastasis from clear cell renal cell carcinoma to the chest wall after 10 years: A case report. Issue 19 (May 2018) - Jiang, Chunyang; Zhao, Shan; Yang, Bingjun; Tang, Tao; Hou, Ruipeng; Liu, Xiaoqin; Zhao, Hui
Abstract: Rationale: Clear cell renal cell carcinoma (CCRCC) is an aggressive tumor associated with a high risk of metastasis and very low survival rate. In addition, it can cause extensive blood metastasis to the lungs, bones, and other organs. Chest wall metastatic tumors from primary CCRCC are rare. Patient concerns: In this report, we present a case of metastatic chest wall tumor that originated from a CCRCC. Diagnoses: An 86-year-old man was diagnosed with chest wall tumor using chest computed tomography. After collecting tissues from the chest wall tumor via needle biopsy, the pathological examination was combined with positive immunoreaction of CD10, epithelial membrane antigen, and vimentin, and the patient was diagnosed with metastatic CCRCC in the chest wall deposits. Interventions: The patient received radiotherapy at 2.0 Gy per time for 25 times. Outcomes: Following 2 months of treatment, the chest wall tumor had shrunk by about one-third of its size. Lessons: Our patient developed a metastatic chest wall tumor that originated from a CCRCC for which right nephrectomy had been performed 10 years previously. Although as per the literature, chest wall metastasis from CCRCC is very rare, it is important to consider tumor metastasis after several years of treatment for precise diagnosis and proper treatment.